Identifikasi Sikap Percaya Diri Siswa Kelas V di SDN Gugus 1 Kecamatan Brang Rea - Riatulhilal; Darmiany; Nurwahidah; Fitri Puji Astria (Action Research Journal, 2025)
The research aims to describe the self-confident attitude of class V in the 20214/2025 academic year. The study used a Quantitative descriptive approach. Involving 96 student from V elementary school, data was collected through a validated questionnaire using a Likert scale. The result of analysis showed that the average percentage of The results of the analysis show that the overall level of student self-confidence is in the High category with an average percentage of 74.8%. The indicators of Confidence in One's Own Abilities and Positive Self-Concept show very high percentages, reaching 80.12% and 80.15% respectively. Meanwhile, indicators of independence in making decisions and daring to express opinions are also in the High category with percentages of 68.62% and 73.43%. Factors that contribute to students' levels of self-confidence include a positive environment, parental support, interaction with peers, and academic experience and achievement. These findings provide an important picture of students' self-confident attitudes and their implications for the development of learning strategies that can increase students' self-confidence